Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Klinik Praktek Dokter Hewan Bersama Alam Sutera Tangerang Selatan - Ardilianto, Candra; Praditya, Alvin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine how the influence of service quality and price on customer satisfaction at the Alam Sutera Joint Animal Practice Clinic, South Tangerang, both partially and simultaneously. The method used in this study is a quantitative method with a sample population of 99 respondents. Data collection techniques using questionnaires and data analysis techniques in this study are validity tests, reliability tests, simple linear regression tests, multiple linear regression tests, correlation coefficients, determination coefficients, partial T tests and simultaneous F tests. The results of the linear regression equation between service quality and price on customer satisfaction are Y = 7.073 + 0.197 X1 + 0.620 X2. The correlation coefficient is 0.768 with an interval between 0.600 - 0.799 which indicates a strong relationship. The coefficient of determination obtained R square of 0.589 means that service quality and price together have a contribution of 58.9% to customer satisfaction. While the remaining 41.1% is influenced by other variables not examined in this study. The results of the partial t test show that the variable of Service Quality on Customer Satisfaction where the calculated t value is 7.665 > t table 1.661 with a significant level of 0.000 < 0.05. This means that Service Quality has a positive effect on Customer Satisfaction. The partial t test of the Price variable on Customer Satisfaction where the calculated t value is 11.195 > t table 1.661 with a significant 0.000 < 0.05. This means that Price has a positive effect on Customer Satisfaction. The results of the simultaneous F test obtained a calculated F value of 66.807 > F table 3.09. This is also strengthened by a significant level of 0.000 < 0.05. So it can be said that Service Quality and Price have a simultaneous effect on Customer Satisfaction at the Joint Veterinary Practice Clinic Alam Sutra South Tangerang Keywords: Service Quality, Price, Customer Satisfaction